EDUKASI KESEHATAN SEKSUAL PADA REMAJA DENGAN MENINGKATKAN PENGETAHUAN DAN SIKAP TERHADAP PENCEGAHAN PELECEHAN SEKSUAL DI SMPN 6 TIMANG GAJAH KABUPATEN BENER MERIAH - Bina Hayati; Muzaffar; Nurlaely HS (LLDIKTI WILAYAH XIII, 2026)
Sexual abuse that occurs in adolescents can be caused by various factors. In children and adolescents, sexual abuse in victims can occur because victims lack supervision and protection from the next of kin, lack of parental care and economic level factors, as well as lack of public awareness to prevent sexual violence against adolescents. This study was conducted to improve the knowledge and attitudes of adolescents. Improving the knowledge and attitudes of adolescents SMPN 6 Timang Gajah against sexual harassment through sexual health education, so as to form awareness and more positive behavior in preventing and avoiding sexual harassment among adolescents. The type of research used in this study is quasi-experimental. The population in this study is all students with seventh and eight grade. Samples in this study were taken by total sampling technique. Based on statistical analysis using the wilcoxon test, obtained the value of p-value 0.000 < ③ 0.05, then ha is accepted and H0 rejected. Thus it can be concluded that there is an influence of sexual health education in adolescents by increasing knowledge and attitudes towards the Prevention of sexual harassment in SMPN 6 Timang Gajah. Keywords: Sexual Health Education, Knowledge, Attitudes, Prevention Of Sexual Harassment